SQL Query Design Patterns and Best Practices : A practical guide to writing readable and maintainable SQL queries using its design patterns /: A practical guide to writing readable and maintainable SQL queries using its design patterns. (2023) - Hughes, Steve; Neer, Dennis; Dr, Singh, Ram Babu; Mala, Shabbir H; Andrews, Leslie; Zhang, Chi
No abstract available